2018
DOI: 10.1038/s41380-018-0231-1
|View full text |Cite
|
Sign up to set email alerts
|

Memory and cognition in schizophrenia

Abstract: Episodic memory deficits are consistently documented as a core aspect of cognitive dysfunction in schizophrenia patients, present from the onset of the illness and strongly associated with functional disability. Over the past decade research using approaches from experimental cognitive neuroscience revealed disproportionate episodic memory impairments in schizophrenia (Sz) under high cognitive demand relational encoding conditions and relatively unimpaired performance under item-specific encoding conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(108 citation statements)
references
References 121 publications
(122 reference statements)
1
90
0
2
Order By: Relevance
“…Since psychotic patients show elevated responses to AMPH without any prior drug exposure 1 , psychosis has been conceptualized as a state of "endogenous sensitization" 10,17,18 . The prefrontal cortex (PFC), origin of reciprocal regulatory connections to subcortical DA neurons 19 , has often been found to be structurally and functionally impaired in SCZ 20,21 . Earlier studies have shown particularly strong relationships between subcortical DA metabolism and the lefthemispheric dorso-lateral PFC (DLPFC) and inferior frontal gyrus (IFG) in SCZ and subjects at-risk mental state for SCZ 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Since psychotic patients show elevated responses to AMPH without any prior drug exposure 1 , psychosis has been conceptualized as a state of "endogenous sensitization" 10,17,18 . The prefrontal cortex (PFC), origin of reciprocal regulatory connections to subcortical DA neurons 19 , has often been found to be structurally and functionally impaired in SCZ 20,21 . Earlier studies have shown particularly strong relationships between subcortical DA metabolism and the lefthemispheric dorso-lateral PFC (DLPFC) and inferior frontal gyrus (IFG) in SCZ and subjects at-risk mental state for SCZ 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…The various subregions of the PFC are involved in deficits in specific cognitive domains 16 . For example, although ventro-lateral PFC functioning remains largely unaffected, impaired dorsolateral (dl)PFC-dependent processes are thought to underlie a range of cognitive deficits in SZ [17][18][19] . In addition, dlPFC activation during the performance of cognitive tasks is decreased in SZ patients 18,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Various regions of the brain are involved in executive memory. The medial temporal lobe (hippocampal system), prefrontal cortex, diencephalon (papillary body and thalamus), and amygdala are reciprocally connected and associated with learning and memory ( Naya et al, 2017 ; Shirayama et al, 2017 ; Guo et al, 2019 ). Short-term memory (including working memory) and long-term memory are separate systems.…”
Section: Discussionmentioning
confidence: 99%